The perils and dangers of these knights (and undead peasants): Interpreting English and Scottish Extent Rolls of 1297–1305. Issue 1 (May 2016) - Donnelly, J.
Abstract : Medieval Scottish economic and social history has held little interest for a unionist establishment but, just when a recovery of historic independence begins to seem possible, this paper tackles a (perhaps the) key pre-1424 source. It is compared with a Rutland text, in a context of foreign history, both English and continental. The Berwickshire text is not, as was suggested in 2014, a 'compte rendu' but rather an 'extent', intended to cross-check such accounts. Read alongside the Rutland roll, it is not even a single 'compte' but rather a palimpsest of different sources and times: a possibility beyond earlier editorial imaginings. With content falling (largely) within the time-frame of the PoMS project (although not actually included), when the economic history of Scotland in Europe is properly explored, the sources discussed here will be key and will offer an interesting challenge to interpretation. And some surprises about their nature and date.